IFPRI Policy Seminar "Beyond Gender Myths: Closing the Knowledge Gap in Agriculture and Food Security" by Terri Raney - Raney, Terri (2013)
IFPRI Policy Seminar ""Beyond Gender Myths: Closing the Knowledge Gap in Agriculture and Food Security" Presentation by Terri Raney, Senior Economist, Food & Agriculture Organization of the United Nations (FAO) at IFPRI on 22 November 2013.